2003
DOI: 10.1128/aem.69.12.6961-6968.2003
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Community Responses of EstablishedGrassland Bacterial Populations to WaterStress

Abstract: The effects of water stress upon the diversity and culturable activity of bacterial communities in the rhizosphere of an established upland grassland soil have been investigated. Intact monoliths were subjected to different watering regimens over a 2-month period to study community adaptation to moisture limitation and subsequent response to stress alleviation following rewetting. Genetic diversity was analyzed with 16S-based denaturing gradient gel electrophoresis (DGGE) of total soil-extracted DNA (rRNA gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(91 citation statements)
references
References 51 publications
7
83
0
1
Order By: Relevance
“…This was similar to the observations that microbial communities could withstand the Cu or water stress with physiological tolerance (Griffiths et al, 2003;Deng et al, 2009).…”
supporting
confidence: 76%
“…This was similar to the observations that microbial communities could withstand the Cu or water stress with physiological tolerance (Griffiths et al, 2003;Deng et al, 2009).…”
supporting
confidence: 76%
“…In contrast, cessation of grazing led first (within o5 months) to a decrease in nitrifier activity and AOB abundance, and only later to a change in community structure. Similarly, Griffiths et al (2003) reported important physiological effects of water stress on the activity of microbial community in grassland soil without any detectable effect on the structure of the microbial community. Thus, the decrease in nitrification observed early for the G-U treatment was likely due to partial starvation and decrease in the abundance of AOB initially present.…”
Section: G -G V S U -Umentioning
confidence: 99%
“…Changes in soil moisture can influence soil microbial community structure via its effects on plant biomass and root exudation. To date only a few studies have been conducted to assess the impact of soil moisture content on soil microbial communities, as influenced by plant community composition (Lundquist et al, 1999;Söderberg et al, 2002;Fierer et al, 2003;Griffiths et al, 2003), although plant diversity is the rule in natural ecosystems rather than the exception of cultivated grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in soil moisture may affect the function and structure of the soil microbial community through its effect on osmotic potential, transport of nutrients and energy, and cellular metabolism, as well as on the competitive interactions between microbial species (Harris, 1981;Yancey et al, 1982;Kempf and Bremer, 1998;Williams and Rice, 2007). Different types of microorganisms are differently affected by changing water potential (Todd et al, 1999;Griffiths et al, 2003;Drenovsky et al, 2004). For example, Gram-negative bacteria are thought to be sensitive to the changes in soil moisture, whereas, fungi are considered more tolerant to low water availability (Harris, 1981;Nesci et al, 2004;Williams and Rice, 2007).…”
Section: Introductionmentioning
confidence: 99%